Implementation of a Psycho-oncology Service in a public hospital of Southeast Brazil: between politics and the COVID-19 pandemic - Daniel Paixão Pequeno; Karla Cristina Gaspar; Carmen Silvia Passos Lima; Gustavo Jacob Lourenço (Brazilian Journal of Oncology)
Introduction: The implementation of a Psycho-oncology Service depends on institutional, structural, and political factors affecting the availability and quality of this service. Recent events, such as the discontinuation of the Professional Improvement Course, a funding source that supports the training of health professionals, and the ongoing COVID-19 pandemic, have had a significant negative impact on the quality of care available to cancer patients. Objectives This experience report aims to describe the establishment of the Psycho-oncology Service within the Clinical Oncology Service of the General Hospital of our University and present the psychosocial impact generated by the termination of Professional Improvement Course and the ongoing COVID-19 pandemic on the lives of cancer patients. Material and Methods: In order to obtain the required data for this report, interviews were held with the heads of the medical and psychological teams of the Clinical Oncology Service. The Hospital Informatics Service provided data on the number of consultations held in the Clinical Oncology Service. A t-test was performed to analyze any differences in consultation numbers. Results: The Psycho-oncology Service was created in 2007, 21 years after the beginning of the Clinical Oncology Service. From 2007 to 2021, there were 22,235 psychology consultations, attending over 8,900 patients. The termination of the Professional Improvement Course funding led to a decrease of 41.9% in the number of consultations per month in our service. The COVID-19 pandemic led to a decrease of about 87.0% in the number of consultations per month in our service. Conclusion: The Professional Improvement Course closing and the COVID-19 pandemic have significantly affected the care for cancer patients and their families and caregivers treated at the aforementioned service.